PRIVATE HEALTH INSURANCE OWNERSHIP IN A SOCIAL HEALTH INSURANCE DOMINATED SYSTEM - Putri, Dinda Bella; Idris, Haerawati; Alyousef, Mohammed (Universitas Airlangga, 2025)
Background: Private health insurance coverage in Indonesia remains very limited, which may increase financial vulnerability despite the dominance of social health insurance. Aims: This study examines factors associated with private health insurance ownership among the Indonesian population. Methods: A cross-sectional study was conducted using data from the 2023 National Socio-Economic Survey (SUSENAS), including 179,339 respondents aged 15–64 years. Multiple logistic regression was applied to estimate adjusted prevalence ratios (PRs) and 95% confidence intervals, controlling for demographic, socioeconomic, and health-related factors Results: The prevalence of private health insurance ownership was 0.5%. Higher education, married status, rich economic status, exposure to internet media, and absence of health complaints were significantly associated with a higher likelihood of ownership. In contrast, respondents aged 25–34 years, those living in households with fewer than five members, and employed individuals were significantly less likely to own private health insurance. Rich economic status was the strongest predictor of private health insurance ownership (adjusted PR = 3.353; 95% CI: 1.997–5.627). Conclusion: Private health insurance ownership in Indonesia is strongly shaped by socioeconomic characteristics and information exposure. These findings provide empirical evidence to support further investigation into the role of private health insurance as a complementary mechanism within Indonesia’s social health insurance-dominated system. Keywords: Indonesia, ownership, private health insurance, socioeconomic factors